PENYULUHAN AKUNTANSI BISNIS SYARIAH KEWIRAUSAHAAN DI MASA PANDEMI COVID-19 DI KAMPUNG CENGAL, DESA KARACAK, KECAMATAN LEUWILIANG, KABUPATEN BOGOR - Rully Trihantana; Ermi Suryani; Siti Halimatussa’diyah (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
The Tridharma of higher education regulates tertiary institutions to care about every problem that exists in the community and is required to try to produce solutions to each of these problems. One of them is through community service activities. One model of community service that focuses on empowering the community's economy in the aspects of education, health, entrepreneurship and the environment. Simultaneously with the occurrence of the Covid-19 pandemic, sharia business accounting counseling was carried out to support the community's economic activities that were already running, and this meant that the community was assisted to manage income and expenses made in carrying out entrepreneurship that had been carried out so far, especially in the midst of the Covid pandemic -19.